Various types of Estonian top‐managers - Tafel, Külliki; Alas, Ruth (Journal of Business Economics and Management, 2007)
Although there is no substantial change on this side, that leaders achieve results through the others work, there are still differences in the way, how leader achieves this. Based on empirical data from Cross Cultural CEO project this paper aims to classify leaders of Estonian organizations. The empirical study involved interviews with CEOs of 63 companies and questionnaires completed by the CEOs and their subordinates. Two types of top managers were received: directive type and team player. Self‐organizing theory has been applied for interpreting results. Implications are developed for leadership development in countries in transition. First Published Online: 14 Oct 2010